Influence of socioeconomic background on cardiovascular disease risk factors among adult Malaysians / Mohammadreza Amiri - Mohammadreza, Amiri (2016)
Developing countries are experiencing more serious cardiovascular disease (CVD) related mortality and morbidity rates than the developed economies, which has been argued to be caused primarily by low education levels and limited access to healthcare facilities. As a developing nation, Malaysia is no different as it has experienced a dramatic increase in the prevalence of CVD risk factors that has raised concerns among policy makers. In light of the aforementioned concerns, this study aims to: i) provide a comprehensive assessment of CVD risk factors (CVDRF), both individually and cumulatively, based on socioeconomic status (SES) determinants (i.e., educational attainment, income level, and occupational status); ii) estimate a ten-year CVD risk (CVDR) assessment based on demographic and SES stratifications; and, iii) evaluate and propose a socioeconomic intervention framework to tackle CVDRF in Malaysia. A representative sample of Malaysian adults participated in the REDISCOVER Study in 2007-2010. Important CVDRFs were included, namely, hypertension, diabetes, and smoking [which constitute cumulative CVDRF1 (CCVDRF1)], and overweight/obesity and hypercholesterolemia [which constitute cumulative CVDRF2 (CCVDRF2)]. The SES indicators were obtained from face-to-face interviews. Various statistical methods, including age-standardization, binary logistic regression and the Karlson, Holm and Breen mediation method were deployed for this study. The prevalence of CCVDRF1 was greater in men than women, while women experienced higher CCVDRF2 than men. Middle-income Malaysians are more likely to be hypertensive, hypercholesterolemic, and obese compared to low-income Malaysians. Skilled professionals are more likely to smoke compared to persons holding other occupations. While the ten-year CVDR increased by age, men had higher predicted risk of CVD compared to women. Ethnically, Malays’ likelihood of having CVDRF was greater than Chinese and Others. Respondents iii with lower levels of income and education had the highest mean and median predicted CVDR factors compared to others. Occupations related to elementary education levels had the highest CVDR compared to other job types. The CCVDRF findings varied in which CCVDRF1 was inversely associated with SES levels, while CCVDRF2 had a direct relationship with SES levels. The results also show that income can mediate the association between education and CCVDRFs. The strongest mediation effect of income level in CCVDRFs was among secondary educated females (52%), Malays (44%), and all sample respondents (37%). Whereas income accounted for 50, 48, and 42 percent of the mediation effect among tertiary males, overall sample respondents, and rural residents respectively in the association between education and CCVDRF2. The results show that low SES respondents will experience greater CVDR in ten years from now. In conclusion, the findings of this study lead to three types of policies that can help the reduction and prevention of CVDR. First, policies must focus more on the lower SES Malaysians to reduce their CVDRFs. Reducing future CVDR, policies should target males, Malays, and the low SES population. Finally, increasing both income and education levels may enhance a reduction in CCVDR morbidities in Malaysia in particular, and the developing world in general.